Sistem Monitoring Tanah Longsor Berbasis Internet of Things dan Geographic Information System - Putra, Roni Wahyu; Suryamen, Haris (Universitas Andalas, 2019)
Landslide is one of the natural disasters that happens quite often in many parts of Indonesia. Landslide brings negative aspects to people because it causes material loss and loss of life. Landslides generally occur in the rainy season with high rainfall. In this research, a system is made to predict the chance of landslide to happen by measuring the level of rainfall, soil moisture, and soil displacement, and send the sensor data and position of a landslide to the database. According to this research, the system can predict the chance for the landslide to happen and give a warning with a 100% success rate.